Vibrational structure of the S(2) (1B(u)) excited state of diphenyloctatetraene observed by femtosecond stimulated Raman spectroscopy. - Kukura, P; McCamant, D; Davis, P; Mathies, R (2003)
Femtosecond time-resolved stimulated Raman spectroscopy (FSRS) is used to study the vibrational structure and dynamics of the S(2) state of diphenyloctatetraene. Strong vibrational features at 1184, 1259 and 1578 cm(-1) whose linewidths are determined by the S(2) electronic lifetime are observed at early times after photoexcitation at 397 nm. Kinetic analysis of the integrated Raman intensities as well as the transient absorption reveals an exponential decay of the S(2) state on the order of 100 fs. These results demonstrate the ability of FSRS to study the vibrational structure of excited state and chemical reaction dynamics on the femtosecond timescale.